IMPACT OF LACTOPEROXIDASE SYSTEM ON Listeria monocytogenes - SARKAR, AVIJIT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2018)
Listeria monocytogenes is highly present in raw milk and dairy waste .It’s also present in cheese received from retail shops. Objective of this experiment was to study the inhibition of Listeria monocytogenes by lactoperoxidase system in milk. Lactoperoxidase, potassium thiocyanate, glucose and glucose oxidase were added as per required concentration to generate the L-P system. Listeria monocytogenes strain 4e was taken under study and Escherichia coli strain NCTC 9703 was taken as positive control in the experiment. Colony count of Listeria monocytogenes fell from an average of 2 x 104 c.f.u /ml to an average of 2.5 x 103 c.f.u/ml within 5 days of storage. As per the study, non-lethal effect of L-P system was observed on L. monocytogenes.